An Experimental Evaluation of Competing Age-Predictions of Future Time Perspective between Workplace and Retirement Domains - Kerry, Matthew J.; Embretson, Susan E. (Frontiers in Psychology, 2018)
Future time perspective (FTP) is defined as “perceptions of the future as being limited or open-ended” (Lang and Carstensen, 2002; p. 125). The construct figures prominently in both workplace and retirement domains, but the age-predictions are competing: Workplace research predicts decreasing FTP age-change, in contrast, retirement scholars predict increasing FTP age-change. For the first time, these competing predictions are pitted in an experimental manipulation of subjective life expectancy (SLE). A sample of N = 207 older adults (age 45–60) working full-time (>30-h/week) were randomly assigned to SLE questions framed as either ‘Live-to’ or ‘Die-by’ to evaluate competing predictions for FTP. Results indicate general support for decreasing age-change in FTP, indicated by independent-sample t-tests showing lower FTP in the ‘Die-by’ framing condition. Further general-linear model analyses were conducted to test for interaction effects of retirement planning with experimental framings on FTP and intended retirement; While retirement planning buffered FTP’s decrease, simple-effects also revealed that retirement planning increased intentions for sooner retirement, but lack of planning increased intentions for later retirement. Discussion centers on practical implications of our findings and consequences validity evidence in future empirical research of FTP in both workplace and retirement domains.